2015
DOI: 10.12659/aot.892754
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain in Renal Transplant Recipients in a Polish Single Centre

Abstract: BMI increases significantly after RT and is associated with higher risk of NODAT, but most RTRs are not aware of their BMI. Therefore, educational programs for this patient population should be created.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Pre-transplant weight is an important factor to be considered when dealing with kidney transplant patients. Two recent studies reported that 29% and 38% of patients on the waitlist for renal transplantation were diagnosed as overweight or obese, respectively [32,33]. In our study, the prevalence of overweight or obesity pre-transplantation was even higher (approximately 43.5%), reaching a prevalence of 55.1% at 12 months post-transplantation.…”
Section: Plos Onesupporting
confidence: 43%
“…Pre-transplant weight is an important factor to be considered when dealing with kidney transplant patients. Two recent studies reported that 29% and 38% of patients on the waitlist for renal transplantation were diagnosed as overweight or obese, respectively [32,33]. In our study, the prevalence of overweight or obesity pre-transplantation was even higher (approximately 43.5%), reaching a prevalence of 55.1% at 12 months post-transplantation.…”
Section: Plos Onesupporting
confidence: 43%
“…It was previously shown that KTRs gain an average of 4.1 kg of weight during the first year after transplantation, which constitutes about 7% of their BMI. Since the majority of KTRs showed insufficient knowledge about overweight or obesity prevention and possible consequences, including hypertension, appropriate educational programs should be considered for this group of patients [ 21 ]. Another risk factor for post-transplant hypertension in KTRs is donor age [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A special population among obese patients is a subgroup of those who undergo organ transplantation. The high prevalence of obesity among those patients is mainly due to the fact that obesity promotes end-stage organ disease, and that transplantation causes an increase in body weight [ 5 , 6 ]. A body mass index (BMI) > 40 kg/m 2 is a contraindication for listing in many transplant programs, and some will not accept patients with a BMI > 35 kg/m 2 until they lose weight.…”
Section: Introductionmentioning
confidence: 99%